Raising teachers’ awareness about English and English as a lingua franca. - Enric Llurda; Yasemin Bayyurt; Nicos Sifakis (Peter Garrett and Josep M. Cots (Eds.), The Routledge Handbook of Language Awareness., 2018)
In this chapter, we will provide a review of the major aspects related to teacher awareness, with special reference to non- native teachers’ awareness of English as an International Lingua Franca (ELF), and will then provide an account of a hands on practical approach aimed at introducing teachers in Expanding Circle countries (Kachru, 1985 ) to the challenges and implications of teaching a global language, thus transforming them into ELF- aware teachers who will be ready to convey such awareness among their students. We will focus on non- native English- speaking teachers’ (NNESTs’) awareness of the global properties of ELF. In order to support our suggestions in the light of a new model of transformative teacher education (Sifakis, 2007, 2014), we provide evidence from an on- going project on ELF- aware language teaching, and we report NNESTs’ perspectives on what they consider to be an ELF- aware lesson, as well as teachers’ observations of how successful they were in raising their students’ awareness towards ELF (Bayyurt and Sifakis, 2015a , 2015b; Sifakis, 2014 ; Sifakis and Bayyurt, 2015).